Model Rekayasa Sistem Pembiayaan Industri Alternatif dalam Mendukung Industri Pengolahan Limbah Plastik - Yana, Syaifuddin; Rusmina, Cut; Maksalmina, Maksalmina; Maryam, Maryam; Nengsih, Rita; Nurfiqi, Aisyah (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Plastic waste processing businesses play a strategic role in supporting environmental sustainability and the development of a circular economy. However, business development in this sector continues to face limited access to financing due to enterprise characteristics dominated by MSMEs, relatively high risk levels, and the mismatch of conventional financing schemes. This article aims to examine and synthesize the literature related to the development of alternative financing systems for plastic waste processing businesses. The method employed is a literature review using a descriptive–analytical approach to various relevant scientific sources and policy reports. The findings indicate that alternative financing mechanisms such as microfinance and cooperatives, partnership-based financing, Islamic financing, crowdfunding, impact investing, as well as government and CSR support have significant potential to improve access to financing for plastic waste processing enterprises. This article also proposes a conceptual model for the development of an integrated alternative financing system involving business actors, financial institutions, markets, and regulatory support. These findings provide important implications for the formulation of green financing policies and the advancement of future research on environmentally oriented business financing